Reactor Laboratory Experiments at Kyoto University Critical Assembly - Pyeon, Cheol Ho.; Chiba, Go.; Endo, Tomohiro; Watanabe, Kenichi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access is an educational text on reactor physics experiments and is described based on a careful examination of the contents and pedagogical benefits obtained from the book Nuclear Reactor Physics Experiments by T. Misawa, H. Unesaki, and C. H. Pyeon (2010) from Kyoto University Press, Japan. The current volume comprehensively covers basic and applied topics on experiment using nuclear reactors, including exponential experiment, uranium enrichment measurement and subcriticality measurements, in addition to approach-to-criticality experiment, control rod calibration experiment, and reaction rate measurement by the activation foil method. This book is intended for graduate students who have already studied reactor physics and radiation detection in an undergraduate program. Readers who have not yet studied these two areas or who wish to review them are recommended to read the companion book Introduction to Nuclear Reactor Experiments, by G. Wakabayashi, T. Yamada, T. Endo, and C.H. Pyeon (2023) from Springer, covering basic concepts and theories of reactor physics and radiation detection. This volume provides a systematic understanding of reactor physics experiments, complemented by its companion book by Wakabayashi et al.
Kyoto University Critical Assembly -- Basics of Reactor Physics -- Approach to criticality Experiment -- Control Rod Calibration Experiments -- Measurements of Reaction Rate -- Determination of Neutron Flux -- Exponential Experiments with Natural Uranium -- Measurement of Uranium Enrichment -- Neutron Detection -- Measurements of Subcriticality.
Keywords: Nuclear physics; Nuclear engineering; Nuclear Physics; Nuclear Energy